EATING ALONE AND FRAILTY AND MENTAL ILL-HEALTH AMONG JAPANESE OLDER ADULTS LIVING IN A METROPOLITAN AREA. (11th November 2018) - Shinkai, S; Seino, S; Tanaka, I; Tomine, Y; Nishi, M; Yokoyama, Y; Kitamura, A
Abstract: Background: It remains unknown whether the negative effect of eating alone in old ages is independent from living arrangement. Methods: 11, 925 older adults who lived in Ota City, Tokyo responded to a mail survey (response, 77%). Physical and mental health were assessed by the "Kaigo-Yobo Checklist (CL15)" and WHO-5, respectively. Eating alone was defined by the answer "alone" to the question "do you usually have meals together?" According to eating status and living arrangement, they were classified into four groups; living with and eating with others (reference group; 3, 905 men and 3, 546 women), living with others but eating alone (221 men, 220 women), living alone but eating with others (235 men, 684 women), living alone and eating alone (550 men, 556 women). The multi-level logistic regression analysis was used to examine independent associations of eating alone with frailty (CL15, 4 or more) and mental ill-health (WHO-5, less than 13). Results: In men, the multivariate-adjusted odds ratios for frailty were 1.74(95%CI, 1.26–2.41) for those living with others but eating alone, 1.08(0.71–1.65) for those living alone but eating with others, 1.74(1.22–2.48) for those living alone and eating alone. In women, the respective values were 2.09(1.50–2.92), 0.89(0.67–1.18) and 1.10(0.83–1.45). Likewise, the multivariate-adjusted odds ratios for mental ill-health were 1.64(1.18–2.28), 1.38(0.93–2.06) and 1.51(1.07–2.14) in men, and 1.56(1.12–2.19), 0.87(0.67–1.14) and 1.35(1.03–1.76) in women. Conclusion: In both sexes, the negative effects of eating alone on frailty and mental ill-health were more prominent in older persons living with others than in those living alone.